(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper analyzes the phenomenon of alliances and military coalitions participated by Celtiberians and other inland communities of Iberia from the beginning of the Second Punic War to the end of the Celtiberian and Lusitanian wars. By systematizing the literary evidence, strictly local or regional coalitions —constituted only by Hispanic actors— are studied, in order to determine the bases of their internal cohesion, the mechanisms of leadership and their purpose.